Methods of Natural Sciences in the Study of Dyes in Manuscripts (On the Example of Inks) - Tereschenko, Elena Yu.; Balachenkova, Aleksandra P.; Tsypkin, Denis O. (Actual Problems of Theory and History of Art, 2022)
The article discusses modern scientific methods used in the study of dyes (inks) used in historical manuscripts. Focusing on the necessity to research a large amount of manuscripts to obtain significant historical and technological information, the screening methods which give the integral characteristics of the handwritten monuments are the following: multispectral imaging for the analysis of the change in text absorption in different ranges of the optical spectrum, qualitative X-ray fluorescence analysis of the main elemental composition, and optical spectroscopy (IR and Raman). The article also describes the methods that make it possible to obtain more detailed in-depth information about the organic and inorganic components of the ink, which are currently at the stage of proving or test studies of both model samples and authentic manuscripts. These research techniques can be used for the elemental composition analysis (PIXE, ICP-AAS and ICP-MS), for the identification of organic components (methods of chromatography with mass spectrometry), for revealing the micro morphology of ink traces (electron microscopy), for the analysis of iron-containing chemical compounds (XAS), and for non-destructive imaging (X-ray / synchrotron tomography). The article was prepared with the financial support of the Russian Science Foundation (grant no. 22-18-00615) in terms of the analysis of methods used for screening studies of historical inks, and the thematic plan of the National Research Center “Kurchatov Institute” in terms of the analysis of natural scientific methods potentially applicable to the study of inks.